Phenotypic and Phylogenetic Characterization of Ruminal Tannin-Tolerant Bacteria - Nelson, Karen E. (American Society for Microbiology, 1998)
The 16S rRNA sequences and selected phenotypic characteristics were determined for six recently isolated bacteria that can tolerate high levels of hydrolyzable and condensed tannins. Bacteria were isolated from the ruminal contents of animals in different geographic locations, including Sardinian sheep (Ovis aries), Honduran and Colombian goats (Capra hircus), white-tail deer (Odocoileus virginianus) from upstate New York, and Rocky Mountain elk (Cervus elaphus nelsoni) from Oregon. Nearly complete sequences of the small-subunit rRNA genes, which were obtained by PCR amplification, cloning, and sequencing, were used for phylogenetic characterization. Comparisons of the 16S rRNA of the six isolates showed that four of the isolates were members of the genus Streptococcus and were most closely related to ruminal strains of Streptococcus bovis and the recently described organism Streptococcus gallolyticus. One of the other isolates, a gram-positive rod, clustered with the clostridia in the low-G+C-content group of gram-positive bacteria. The sixth isolate, a gram-negative rod, was a member of the family Enterobacteriaceae in the gamma subdivision of the class Proteobacteria. None of the 16S rRNA sequences of the tannin-tolerant bacteria examined was identical to the sequence of any previously described microorganism or to the sequence of any of the other organisms examined in this study. Three phylogenetically distinct groups of ruminal bacteria were isolated from four species of ruminants in Europe, North America, and South America. The presence of tannin-tolerant bacteria is not restricted by climate, geography, or host animal, although attempts to isolate tannin-tolerant bacteria from cows on low-tannin diets failed.